Empire. The complete third season [videorecording (DVD)] - Hamri, Sanaa; Brewer, Craig; Howard, Terrence; Henson, Taraji P.; Yazz, 1993- (Twentieth Century Fox Home Entertainment, 2017)
Follows music mogul Lucious Lyon who, after he is diagnosed with ALS, must decide which of his family members should take his place as head of the business.